ENTERPRENEURIAL GOVERNMENT DALAM PERSEPSI PEJABAT BIROKRASI - Adyan BP Harahap (Universitas Riau, 2016)
Enterpreneurial Government in the Official Perceptions Bureaucracy. This study aims todescribe and analyze the perspective of bureaucratic officials Dumai City Government in acceptingand understanding the concept of Enterpreneurial Government and to understand the factors thatexplain the understanding and attitude of officials in the government bureaucracy Dumai CityGovernment in accepting the concept Enterpreneurial. In this research uses descriptive quantitativeresearch methods with data collection questionnaire, interviews, observation and documentation. Asa source of data and population are all structural in the city government Dumai using proportionalstratified random sampling and random sampling which is the development of stratified randomsampling. The results showed that the views and knowledge of bureaucratic officials to the conceptof Entrepreneurial Government, as demonstrated by this study is still very low. As demonstrated bythe lack of understanding and knowledge of the principles of community-oriented government. Theirrejection of the idea of citizen charter and the concept of customer choise in terms of public services.